2007
DOI: 10.5194/nhess-7-629-2007
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous radon emanation linked to preseismic electromagnetic phenomena

Abstract: Abstract. Anomalous emanation of radon ( 222 Rn) was observed preceding large earthquakes and is considered to be linked to preseismic electromagnetic phenomena (e.g. great changes of atmospheric electric field and ionospheric disturbances). Here we analyze atmospheric radon concentration and estimate changes of electrical conditions in atmosphere due to preseismic radon anomaly. The increase of radon emanation obeys crustal damage evolution, following a powerlaw of time-to-earthquake. Moreover, the radon eman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 41 publications
(44 reference statements)
2
43
0
2
Order By: Relevance
“…In contrast, Omori et al (2007) argued that the radon emanation increased the number density of small ions and the atmospheric conductivity, consequently decreasing the atmospheric electric field, a view also shared by Harrison et al (2010).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, Omori et al (2007) argued that the radon emanation increased the number density of small ions and the atmospheric conductivity, consequently decreasing the atmospheric electric field, a view also shared by Harrison et al (2010).…”
Section: Discussionmentioning
confidence: 97%
“…If we try to fit the models of Liperovsky et al (2005 and and Omori et al (2007) cited in the Introduction section into the observations in this research, we have the limitation that no radon gas monitoring has been performed in Peru. Mainly because most earthquakes in the country are related to medium depth (in Peru considered from 61 to 300 km) and deep (301-750 km) hypocenters, so far they have not been considered to produce radon gas emanations.…”
Section: Discussionmentioning
confidence: 99%
“…St-Laurent (2000) reported EQLs associated with earthquakes as small as M = 4.8 in Quebec, Canada. Omori et al (2007) have researched on anomalous radon gas emissions associated with electromagnetic phenomena previous to large earthquakes, which could be the case in the large earthquake of 2007 in Pisco, Peru. Recently, Fidani (2010) published a comprehensive study of EQLs associated with the 6 April 2009 Aquila earthquake in Italy in which 241 EQL reports were considered out of 1057 phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, anomalous changes to the ground, atmosphere and ionosphere, observed by both Earth-and space-based instrumentation, were found to be associated with several earthquakes that occurred in China, Taiwan, Europe and Japan (Walia et al 2006, Yasuoka et al 2006, Cioni et al 2007, Omori et al 2007, Sharma et al 2008, Anagnostopoulos et al 2010b, Hayakawa and Hobara 2010, Singh et al 2010a. These recent reported pronounced changes in the various surface and atmospheric parameters a few days prior to various earthquakes provide a strong evidence of lithosphere-atmosphere-ionosphere coupling.…”
mentioning
confidence: 95%
“…During the last 100 years there has been an average of about 18 large earthquakes (magnitude 7.0-7.9) in each year (http://earthquake.usgs.gov). Recent studies using multisensor data have shown that pronounced changes occur on the Earth's surface, meteorological and atmospheric, and ionospheric parameters associated with earthquakes which occurred in China, Russia, Japan, Taiwan and Europe (Liu et al 2000, Matsuda and Ikeya 2001, Cervone et al 2004, Singh et al 2006a,b,c, Walia et al 2006, Yasouka et al 2006, Cioni et al 2007, Dutta et al 2007, Ghosh et al 2007, Omori et al 2007, Inan et al 2008. These changes can be utilized to obtain early information about an impending earthquake.…”
Section: Introductionmentioning
confidence: 99%